Case Report: Lifesaving Hemostasis With Resuscitative Endovascular Balloon Occlusion of the Aorta in a Patient With Cardiac Arrest Caused by Upper Gastrointestinal Hemorrhage - Hashida, Tomoaki; Hata, Nanami; Higashi, Akiko; Oka, Yoshito; Otani, Shunsuke; Watanabe, Eizo (Frontiers in Medicine, 2021)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) is performed to treat hemorrhagic shock, whose cause is located below the diaphragm. However, its use in patients with gastrointestinal hemorrhage is relatively rare. The 45-year-old man with a history of dilated cardiomyopathy had experienced epigastric discomfort and had an episode of presyncope. On his presentation, the patient’s blood pressure was 82/64 mmHg, heart rate 140/min, and consciousness level GCS E4V5M6. Hemodynamics stabilized rapidly with a transfusion that was administered on an emergency basis, and a blood sample only showed mild anemia (Hb, 11.5 g/dL). The patient was admitted to investigating the presyncope episode, and the planned endoscopy was scheduled the following day. The patient had an episode of presyncope soon and was found in hemorrhagic shock resulting from a duodenal ulcer rapidly deteriorated to cardiac arrest. Although a spontaneous heartbeat was restored with cardiopulmonary resuscitation, the patient’s hemodynamics were unstable despite the emergency blood transfusion administered by pumping. Consequently, a REBOA device was placed, resuscitation was continued, and hemostasis was achieved by vascular embolization for the gastroduodenal artery. The patient was subsequently discharged without complications. However, there is no established evidence regarding the REBOA use in upper gastrointestinal hemorrhage, and the investigations that have been reported have been limited. Further, one recent research suggests that appropriate patient selection and early use may improve survival in these life-threatening cases. As was seen in the present case, REBOA can effectively treat upper gastrointestinal hemorrhage by temporarily stabilizing hemodynamics and enabling a hemostatic procedure to be quickly performed during that time. This report also demonstrated the hemodynamics during the combination of intermittent and partial REBOA to avoid the complications of ischemic or reperfusion injury of the intestines or lower extremities.